Impact of active power recovery rate of DFIG wind farms on first swing rotor angle stability - Enkhtsetseg Munkhchuluun; Lasantha Meegahapola; Arash Vahidnia (IET Generation, Transmission & Distribution, 2020)
The first swing rotor angle stability is still an important stability challenge for modern power systems integrated with a large number of renewable energy‐based sources, such as wind farms and solar‐photovoltaic farms. Therefore, innovative strategies must be developed to exploit the full potential of doubly fed induction generators (DFIGs) to improve the first swing rotor angle stability in the system. This study presents a new active power logic (APL) controller for DFIGs which can reduce the active power during the fault and slowly recover it after the fault to allow synchronous generators to increase the electrical power during and after the fault; thus, enabling synchronous generators to improve the first swing rotor angle stability. The feasibility of the proposed control scheme is investigated via theoretical analysis and simulation studies. The reliability and voltage stability test system is used to demonstrate the effectiveness of the proposed scheme for local and remote faults and increased DFIG penetration conditions. The comparative results show that the proposed APL controller of the DFIG improves the first swing rotor angle stability, specifically when the DFIGs are located near the synchronous generators.